Commitment to Online Community and Continuance Intention: Issue Involvement, Interactivity, and Social Interaction - Sony Kusumasondjaja (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
The purpose of this study is to investigate how issue involvement, online interactivity, and social interaction influence consumer commitment to online travel community and intention to continue participating in the community. An online traveling forum was examined as the issues being observed in this study are highly relevant to the forum. Based on 135 valid responses from active members of the forum obtained through distributing online questionnaire in the forum, structural equation modeling was employed to examine the research model. The results show that issue involvement and social interaction affect commitment to the community; while surprisingly social interaction does not have a significant influence on the commitment. Moreover, commitment to the community leads consumers to continue their participation in the community. Managerial contributions and limitations of the study are discussed.